2014
DOI: 10.1097/med.0000000000000085
|View full text |Cite
|
Sign up to set email alerts
|

Immune regulators of inflammation in obesity-associated type 2 diabetes and coronary artery disease

Abstract: Purpose To summarize current work identifying inflammatory components that underlie associations between obesity-associated type 2 diabetes (T2D) and coronary artery disease (CAD). Recent findings Recent studies implicate immune cells as drivers of pathogenic inflammation in human T2D. Inflammatory lymphocytes characterize unhealthy adipose tissue (AT), but regional adipose volume, primarily visceral and pericardial fat; also predict severity and risk for obesity-associated CAD. Having a greater understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 106 publications
1
24
0
Order By: Relevance
“…In line with other observations [16,36], this suggests that the contribution of EAT to the coronary atherosclerotic burden is more relevant in non-obese than in obese patients and raises the issue of whether obesity may conceal the pathogenetic effects of EAT on CAD progression. Alternatively, it can be theorized that the factors mediating the association between EAT and CAD might change when obesity develops [38].…”
Section: The Clinical Relevance Of Eat In Coronary Artery Diseasementioning
confidence: 99%
“…In line with other observations [16,36], this suggests that the contribution of EAT to the coronary atherosclerotic burden is more relevant in non-obese than in obese patients and raises the issue of whether obesity may conceal the pathogenetic effects of EAT on CAD progression. Alternatively, it can be theorized that the factors mediating the association between EAT and CAD might change when obesity develops [38].…”
Section: The Clinical Relevance Of Eat In Coronary Artery Diseasementioning
confidence: 99%
“…Alternatively, it has been postulated that the mechanisms underlying the association between epicardial fat and development of CAD might be different for lean and obese individuals. 31 …”
Section: Association Between Epicardial Fat and Cad: Is It Simply A Pmentioning
confidence: 99%
“…4,10 In fact, in comparison with the Framingham risk score (where smoking and type 2 diabetes mellitus only account for 1.6-and 3-fold risk of having CAD, respectively), pericardial fat volume was identified as the strongest predictor of developing CAD (odds ratio of 4.1). 30,31 In addition, a case-control study identified pericardial fat volume to be a strong predicator of myocardial ischemia in patients without CAD. 32 The question of whether such predictive capabilities can be attributed specifically to epicardial fat has been addressed by recent studies such as the Heinz Nixdorf Recall study, where epicardial fat volume was significantly associated with coronary events over the course of 8 years, even after adjusting for traditional cardiovascular risk factors.…”
Section: Pathophysiological Relevance Of Human Epicardial Fatmentioning
confidence: 99%
“…Obesity is an alarming epidemic because of its comorbidities, which include diabetes, cardiovascular disease [4], and based on new evidence, increased risk of some forms of cancer [5,6]. Obesity-driven diabetes, or Type 2 diabetes, was previously only a problem for adults and was termed "adult-onset" diabetes, to distinguish it from "childhood" diabetes, or Type 1 diabetes, which is primarily immunological in origin.…”
Section: The Pediatric Obesity Epidemic Global Inequality and Currmentioning
confidence: 99%